Natural Convention Analysis of 6061, 6063, 7071 & 356 Alloy Heat Sink for Electronic Gadgets Application - Krishnamoorthy; Jayakumar , T. (Research and Developments in Engineering Research Vol. 2, 2023)
The aim of the current research to investigate the maximum heat dissipation with optimal weight of the heat sink. To dissipate the heat in the electronic chip, the fin design and materials selection as a major factors in heat sink. To increase the reliability of a device, the prediction of its electronic components' possible thermal behavior is essential. Several methods are based on tedious mathematics and formulations that can predict thermal images of electronic components. Accessible exploratory data from the available data for a continuously finned heat sink is used to verify the 3D fin design. To determine the heat sink's mean temperature distribution and method of heat transfer. Results reveal that the 6063 aluminum alloys with case II fin design have maximum heat dissipation of the heat sink compared to 6061, 7071 alloys. The heat dissipation of heat sink case II fin design is greater than the case I fin design under all the material condition, due to the airflow of the design. The mass of the case I fin design is lesser than the case II fin design. But, the case I fins increase the heat transfer rate and have a higher weight than regular case II fin design. In addition to. the case II fin design has the lowest temperature without raising the weight of the heat sink, which implies that the better performance in comparison to the other designs. It is concluded that case II fin design has the lowest temperature without raising the weight of the heat sink, which implies that the better performance in comparison to the other designs.